Budaya Komunikasi Virtual Dalam Aktivitas Live Streaming TikTok - Alamsyah, Puti Alifa Layynasha; Sudradjat, Ratih Hasanah (Universitas Garut, 2025)
Live streaming on TikTok has become a popular phenomenon among Indonesians, with creators and influencers utilizing this feature to interact with audiences through Q&A, scheduled events, and live streaming, resulting in controversial content. TikTok now gives content creators the freedom to develop creativity on TikTok live shows in interacting with their audience. This study aims to explore the culture of virtual communication in live streaming on TikTok. This research uses a qualitative method with a digital ethnography approach to study the dimensions of virtual communication that occur in TikTok Live activities. Data were obtained through observation and in-depth interviews with TikTok Live actors and viewers. This research also uses NVIVO as qualitative data analysis software. This analysis produces 3 types of data visualization, namely coding of reference, contribution on coding and word cloud. The results show that the virtual communication culture that occurs in TikTok live streaming activities as a communication channel creates effects arising from messages and symbols related to attitudes, practical habits, and values that develop in the TikTok Live virtual circle. This research contributes to the understanding of how virtual communication culture develops on social media platforms such as TikTok and TikTok Live.